Impacto dos stents e do sirolimus por via oral na vasomotricidade coronariana dependente e independente do endotélio - Fernandes, Rósley Weber Alvarenga [UNIFESP] (2012)
Rationale: There is no consensus regarding the impact of stenting on long-term endothelial function. There have been reports of increased endothelial dysfunction with Sirolimus-eluting stents as compared to bare metal stenting (SC). Objectives: This study aims to assess the impact of SC and the effect of oral Sirolimus on endothelial function. Methods: Forty-five patients were randomized into three groups: SC + high-dose oral Sirolimus (initial dose of 15 mg, followed by 6 mg/day during four weeks); SC + lowdose Sirolimus (6 mg followed by 2 mg daily during four weeks); and SC without Sirolimus. Changes in vasoconstriction or vasodilation in a 15 mm segment starting at the distal stent end in response to acetylcholine and nitroglycerin were assessed by quantitative angiography. Results: The groups had similar angiographic characteristics. The percent variation in diameter in response to acetylcholine was similar in all groups at the two time points (p = 0.469). Four hours after stenting, the target segment presented an endothelial dysfunction that was maintained after eight months in all groups. In all groups, endothelium-independent vasomotion in response to nitroglycerin was similar at four hours and eight months, with increased target segment diameter after nitroglycerin infusion (p = 0.001). Conclusions: The endothelial dysfunction was similarly present at the 15 mm segment distal to the treated segment, at 4 hours and 8 months after stenting. Sirolimus administered orally during 4 weeks to prevent restenosis did not affect the status of endothelium-dependent and independent vasomotion.